2018
DOI: 10.1111/jcpp.12972
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal structural brain development and externalizing behavior in adolescence

Abstract: BackgroundCross‐sectional studies report relations between externalizing behavior and structural abnormalities in cortical thickness of prefrontal regions and volume reductions in subcortical regions. To understand how these associations emerge and develop, longitudinal designs are pivotal.MethodIn the current longitudinal study, a community sample of children, adolescents and young adults (N = 271) underwent magnetic resonance imaging (MRI) in three biennial waves (680 scans). At each wave, aspects of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 44 publications
2
57
5
Order By: Relevance
“…We also examined age-related two-way and three-way interactions with sex and group for gray matter volume in the vmPFC and amygdala regions-of-interest, and for cortical thickness in the whole-brain analysis. Despite our hypothesis that the relationship between sex, disruptive behavior, and brain structure might differ with age ( Oostermeijer et al, 2016 ; Bos et al, 2018 ; Muetzel et al, 2018 ), no age-related interactions were observed in this study. It is important to note that both of these recent longitudinal structural MRI studies ( Oostermeijer et al, 2016 ; Bos et al, 2018 ; Muetzel et al, 2018 ) did not find significant age-related interactions with disruptive behavior in the ventral prefrontal cortex or amygdala.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…We also examined age-related two-way and three-way interactions with sex and group for gray matter volume in the vmPFC and amygdala regions-of-interest, and for cortical thickness in the whole-brain analysis. Despite our hypothesis that the relationship between sex, disruptive behavior, and brain structure might differ with age ( Oostermeijer et al, 2016 ; Bos et al, 2018 ; Muetzel et al, 2018 ), no age-related interactions were observed in this study. It is important to note that both of these recent longitudinal structural MRI studies ( Oostermeijer et al, 2016 ; Bos et al, 2018 ; Muetzel et al, 2018 ) did not find significant age-related interactions with disruptive behavior in the ventral prefrontal cortex or amygdala.…”
Section: Discussioncontrasting
confidence: 97%
“…Given the influence of age on brain structure development ( Gennatas et al, 2017 ), we also tested age-related differences between DBD and healthy control children (group-by-age interactions) and potential interactions with sex (sex-by-group-by-age interactions). Recent longitudinal structural studies suggest attenuation of cortical maturation (i.e., reduced cortical thinning) and exaggeration of subcortical maturation in the emergence of disruptive behavior in youth ( Oostermeijer et al, 2016 ; Bos et al, 2018 ; Muetzel et al, 2018 ). Thus, even though exploratory in nature, we expected adolescents with DBD to show increased volume and thickness in prefrontal regions compared to younger children with DBD relative to controls, and the opposite pattern for amygdala volume.…”
Section: Introductionmentioning
confidence: 99%
“…That SDP predicted differentiation towards externalizing symptoms is consistent with the generalist gene and specialist environments hypothesis, which suggests that genetic influences should be more predictive of severity of problems and comorbidity, whereas environmental influences should explain their divergence [28,46,47]. Here, we find support that SDP may be a specific environmental influence serving to nudge individuals down developmental trajectories that are more externalizing in nature, perhaps through impairments in brain regions that are linked to behavioral disinhibition (a hallmark of externalizing but not internalizing problems) [48]. Interestingly, the only other predictor of directionality of internalizing/externalizing symptoms in the literature was also a prenatal influence: obstetric complications predicted a preponderance of internalizing relative to externalizing problems.…”
Section: Discussionsupporting
confidence: 84%
“…To compute bilateral measurements of surface area we averaged measurements for left hemisphere (lh) and right hemisphere (rh) surface area (SA): 2 . To compute bilateral measurements of average cortical thickness (CT), we took the size of each region into account (also see Bos et al, 2018 ) by using the following formula:
Fig. 2 Regions of interest in the social brain, including TPJ (blue), pSTS (orange), mPFC (green), and precuneus (yellow).
…”
Section: Methodsmentioning
confidence: 99%